A comparison of mitochondrial DNA isolation methods in frozen post-mortem human brain tissue—applications for studies of mitochondrial genetics in brain disorders. (October 2015) - Devall, Matthew; Burrage, Joe; Caswell, Richard; Johnson, Matthew; Troakes, Claire; Al-Sarraj, Safa; Jeffries, Aaron R; Mill, Jonathan; Lunnon, Katie
Given that many brain disorders are characterized by mitochondrial dysfunction, there is a growing interest in investigating genetic and epigenetic variation in mitochondrial DNA (mtDNA). One major caveat for such studies is the presence of nuclear-mitochondrial pseudogenes (NUMTs), which are regions of the mitochondrial genome that have been inserted into the nuclear genome over evolution and, if not accounted for, can confound genetic studies of mtDNA. Here we provide the first systematic comparison of methods for isolating mtDNA from frozen post-mortem human brain tissue. Our data show that a commercial method from Miltenyi Biotec, which magnetically isolates mitochondria using antibodies raised against the mitochondrial import receptor subunit TOM22, gives significant mtDNA enrichment and should be considered the method of choice for mtDNA studies in frozen brain tissue.